2017
DOI: 10.1016/j.jvsv.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the great saphenous vein with nontumescent n-butyl cyanoacrylate versus endovenous laser therapy

Abstract: The NBCA-based vein sealing system is a fast and effective treatment option for the management of incompetent saphenous veins that does not involve tumescent anesthesia, compression stockings, paresthesia, burn marks, or pigmentation. Further large-scale studies with long-term outcomes are required to identify the optimal treatment modalities for patients with saphenous vein insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 14 publications
1
62
1
2
Order By: Relevance
“…This corresponded with previous findings, 11,12 although one study reported a higher percentage of phlebitis after NBCA (20%). 21 The number of patients with ecchymosis in the RFA group was statistically significantly higher than in the other two groups in the study. Other authors also observed less ecchymosis after NBCA than after thermal ablation with EVLA or RFA.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This corresponded with previous findings, 11,12 although one study reported a higher percentage of phlebitis after NBCA (20%). 21 The number of patients with ecchymosis in the RFA group was statistically significantly higher than in the other two groups in the study. Other authors also observed less ecchymosis after NBCA than after thermal ablation with EVLA or RFA.…”
Section: Discussionmentioning
confidence: 59%
“…Only two prospective studies have compared EVLA and NBCA. 12,21 No significant difference was found between the groups in these studies. The only randomised clinical trial to compare NBCA and RFA was the VeClose trial.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Bozkurt and Yılmaz (11) subsequently compared NBCA with EVA and reported 12-month results. In 2017, Koramaz et al (10) published a study comparing NBCA and EVA, and in 2018 the VeClose study published its 24-month findings. Again in 2018, Yasim et al (8) and Eroglu and Yasim (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving NBCA have been published. Studies have also compared NBCA with other thermal ablation methods (8)(9)(10)(11) . However, no previous studies have compared the two techniques in the same patient.…”
Section: Introductionmentioning
confidence: 99%